Epidemiology and management of paediatric head injury in eastern Nepal - Agrawal A; Agrawal C; Kumar A; Lewis O; Malla G; Khatiwada R; Rokaya P (Wolters Kluwer Medknow Publications, 2008)
Background: In children, majority of the head injuries are minor and management of critically ill children depend on a team approach using well-rehearsed, systematic management protocols that can be implemented within hours after injury. This study was carried out to ascertain the epidemiology and management of know the demographic profile and etiology of paediatric head injury in our setting, to know the clinical and radiological characteristics of head injury patients and to know the treatment options and outcome in paediatric head injuries. Patients and Methods: Details of all children (age < 16 years) with head injury seen in 1 year from 01.04.2005 to 31.03.2006 were retrospectively reviewed. Demographic profile, clinical details, investigations, treatment offered, and outcome were noted in a proforma. All data were analyzed by appropriate SPSS 11.0 statistical software tools. Results: There were total 43 patients. Young male children were more commonly affected in present series with a mean age of 7.67 years (median - 5.010 years), range 6 months-16 year. Fall (65.11%) was the most common mode of injury followed by road traffic accidents (RTAs) (25.6%). Mild head injuries (65.11%) were most common. Most common complaint was loss of consciousness and all the patients with severe head injury presented loss of consciousness. All patients with mild head showed good recovery; with moderate head injury, nine patients showed good recovery and three patients recovered with moderate disability. Patients with severe head injury (three patients) had 100% mortality. Conclusions: In urban areas of Nepal, RTAs like vehicular crashes, motor cycle accidents, and pedestrian hit by moving vehicle are more common and in rural areas fall from height are commoner. We need to develop child safety legislations and risk-specific intervention programs in Nepal.